Optimizing maintenance reliability program for small fleets - Marušić, Željko; Galović, Borivoj; Pita, Omer (Transport, 2007)
Reliability program is considered to be a very valuable means of achieving better operational performance (through decreased maintenance related problems in operation) and increased flight safety. For this reason, reliability programs are mandated by the regulations for all commercial operators. Depending on the size of the operator, implementation of reliability program can be carried out in various organizational forms. Small fleets represent too small a statistical sample to collect enough information for obtaining statistically significant and accurate data. Therefore usability of reliability program in very small fleets is questionable. The aim of this work is to highlight some problems related to maintenance reliability program for small fleets.First Published Online: 27 Oct 2010